Índice de fragilidade do idoso brasileiro: uma abordagem multidimensional - Silva, Mariá Gonçalves Pereira da (2018)
The objective of this work was to construct a Frailty Index (FI) of the Brazilian elderly using population-based data and characterize the frailty with a multidimensional approach. Using the National Health Survey, a Reference FI (IF-R) was calculated which, based on its association with other fragility determinants, originated the Brazilian FI (IF-B), adapted to the Brazilian context. A multiple factor analysis was applied to the determinants of IF-B aiming to characterize the fragility in a multidimensional approach, giving rise to Multidimensional FIs (IF-M). In addition, the FIs were stratified into four frailty groups (non frail, vulnerable, frail and most frail) based on the literature: and compared with the classification agreement between the groups. The three indices (IF-R, IF-B and IF-M) presented better fitting to the gamma distribution with means of 0.13, 0.14 and 0.16, respectively. The classification agreement between the frailty groups given by IF-B with IF-R was 79% and with IF-M was 76%. Concerning the presence of frailty, the agreement between IF-B and IF-R was 94% and between IF-B and IF-M was 92%. These findings show a good agreement between the three indices, however they point out the existence of other dimensions that may be influencing the characterization of the frailty. This suggests the need for continuity of the characterization of the frailty as a multidimensional phenomenon.